Adherence to the physical activity guideline beyond the recommended minimum weekly amount: impacts on indicators of physical function in older adults - Veen, Jort; Edholm, Peter; Rodriguez-Zamora, Lara; Folkesson, Mattias; Kadi, Fawzi; Nilsson, Andreas (Frontiers in Public Health, 2023)
Introduction The extent to which additional health benefits of accumulating twice the minimum amount of time in moderate-to-vigorous physical activity (MVPA) affects indicators of physical function in older adults is unclear. Therefore, the aim of the present study was to assess indicators of physical function in older adults who accumulate at least 150 but less than 300 min/week of MVPA compared to those accumulating at least 300 min/week. Methods Indicators of physical function, including handgrip strength, 5 times sit-to-stand test (5-STS), squat jump and 6-min walk test (6MWT) were assessed in a sample of 193 older men (n = 71, 67 ± 2 years), and women (n = 122, 67 ± 2 years), who all accumulated at least 150 weekly minutes of MVPA. Time in MVPA was assessed by accelerometry during 1 week and engagement in muscle strengthening activities (MSA) was assessed by self-report. Protein intake was assessed by a food-frequency-questionnaire. Participants were classified as physically active (≥150 but <300 min of MVPA per week) or as highly physically active (≥300 min of MVPA per week). Results Factorial analysis of variance revealed that older adults accumulating at least 300 min of MVPA per week had a significantly (p < 0.05) better 6MWT performance and overall physical function compared to the less active group. These findings remained significant after further adjustment for MSA, sex, waist circumference and protein intake. In contrast, no significant differences in indicators of muscle strength were observed between the two groups. Discussion Adherence to twice the recommended minimum amount of weekly MVPA time is related to a better physical function, evidenced by a better walking performance compared to adherence to the minimum weekly amount of MVPA. This finding emphasizes the benefits of accumulating daily MVPA beyond the minimum recommended amount to optimize the ability to perform activities of daily living, thus reducing the burden of physical disability and related health-care costs.